2015
DOI: 10.1016/j.biortech.2014.10.141
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Nizimuddinia zanardini macroalgae biomass composition and its potential for biofuel production

Abstract: zanardini macroalgae biomass composition and its potential for biofuel production, Bioresource Technology (2014), doi: http://dx.doi.org/10.1016/j.biortech. 2014.10.141 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(31 citation statements)
references
References 24 publications
0
30
0
1
Order By: Relevance
“…In the same year of 2011, Jung et al [40] reported that L. japonica contains 55.1 wt.% of hemicellulose, which may be interesting since hemicellulose is the representative component which decomposes during torrefaction for lignocellulosic biomass. The authors are however rather skeptical about such a high hemicellulose content in macroalga, since all other references are telling that the representative saccharides of macroalga are alginate and mannitol [28,33,39]. Also it seems that Jung et al [40] followed a procedure for analyzing hemicellulose, cellulose and lignin contents, which may not be a relevant procedure for marine biomass.…”
Section: Torrefaction Experimentsmentioning
confidence: 94%
See 1 more Smart Citation
“…In the same year of 2011, Jung et al [40] reported that L. japonica contains 55.1 wt.% of hemicellulose, which may be interesting since hemicellulose is the representative component which decomposes during torrefaction for lignocellulosic biomass. The authors are however rather skeptical about such a high hemicellulose content in macroalga, since all other references are telling that the representative saccharides of macroalga are alginate and mannitol [28,33,39]. Also it seems that Jung et al [40] followed a procedure for analyzing hemicellulose, cellulose and lignin contents, which may not be a relevant procedure for marine biomass.…”
Section: Torrefaction Experimentsmentioning
confidence: 94%
“…Current conversion technologies for macroalgae includes mainly biogas production by anaerobic digestion [28,33], bioethanol production [29,33] and lipid production [30]. It is very natural that all the studies above are of the macroalgae utilization technologies which do not need the drying process of macrolagae, since drying process consumes a considerable amount of energy.…”
Section: Introductionmentioning
confidence: 99%
“…Catalytic liquefaction is a promising technology for converting biomass to produce sustainable liquid biofuels and chemicals (Yazdani et al, 2015). Traditional biomass liquefaction has usually been carried out in a stirred tank reactor using inorganic acid/alkali as a catalyst at a temperature higher than 150°C for 60 min or longer.…”
Section: Introductionmentioning
confidence: 99%
“…Physical, chemical, or biological pretreatment methods can be combined to obtain high yields from enzymatic saccharification [14]. In general, pretreatment methods used prior to biological treatment are γ-irradiation [15], chemical treatment (tap water [16], hydrochloric acid [17,18], sulfuric acid [19][20][21], sulfuric acid and hot water [22]), and hydrothermal treatment (distilled water [23], or distilled water and cellulase saccharification [24,25]). Enzymatic saccharification of brown seaweed has been studied using enzymes such as laminarinases [26], alginate lyases [27], commercial cellulase blends [28], and commercial meicelase [29].…”
Section: Introductionmentioning
confidence: 99%